Development of sustainable energy indexes by the utilization of new indicators: A comparative study. (November 2019) - Armin Razmjoo, A.; Sumper, Andreas; Davarpanah, Afshin
Abstract: Decision making to improve energy sustainability requires scientifically information based on sustainability. Since there are different sustainability targets and specific decision problems in this regard, hence to achieve these targets or solve these problems, relevant sustainability indicators are needed. In this study, is investigated and developed a variety of applicable indicators to enhance sustainable energy development index. Indeed, the main aim of this study is to present new effective indicators related to sustainable development goals, investigating the most important challenges related to energy sustainability. Additionally, this work is following to find the main gaps which are as obstacles in achieving energy sustainability for 12 different countries. To do this, firstly the required data from international energy agency (IEA) and world bank gathered and then is analyzed.